SMART TECHNOLOGIES, ALGORITHMIC GOVERNANCE AND DATA JUSTICE - Whelan, Andrew; James, Alexandra; Humphry, Justine; Dreher, Tanja; Hynes, Danielle; Wilcock, Scarlet (AoIR Selected Papers of Internet Research, 2019)
This panel engages critically with the development, application and emerging effects of ‘smart’ technologies of governance. Attending specifically to the ramifications of new forms of (‘big’) data capture and integration implemented by or for state agencies, the panel describes how the rollout of these technologies impacts on and is shaped by contexts prefigured by social and economic inequalities. Two specific arenas are addressed and juxtaposed, with two papers on each of these. The first arena is the introduction of ‘smart city’ technologies and their implications for low income and marginalised communities. Often presented as novel augmentations of urban space, enhancing and customising the urban experience at the same time that they increase the city’s efficiency and ‘awareness’, smart city technologies also reconfigure urban spaces and how they are understood and governed by rendering the city a site of data generation and capture. This presents new opportunities and risks for residents and powerful commercial and state actors alike. The emergence of public wi-fi kiosks as a means of providing internet access to underserved communities, as one panellist describes, can be shown to expose low-income residents to new forms of surveillance and to new kinds of inequity in terms of the asymmetry of information made available to the parties in the exchange at the kiosk. Surveillance and data capture is organised to particular ends and powerful interests shape and leverage the design and affordances of such initiatives in particular ways. Insofar as concerns are raised about these developments, they are commonly framed in terms of individual rights to privacy, missing the scale of the issues involved. It is not merely that ‘opting out’ becomes untenable. As other panellists show, the issues involved are fundamentally social rather than individual in that they foreground questions around the appropriate relations between state and commercial actors, the use and nature of public space, and the uneven distribution of rights of access to space, information, and other resources within the city. Economically disenfranchised groups are not only denied meaningful access and participation, but colonised by data processes designed to extract various forms of value from their use of ‘public’ infrastructure which may not best serve their own interests. The second arena addressed by the panel is the role of algorithmic governance and artificial intelligence in the provision of social welfare. This context is described in terms of both the effects for the frontline service encounter, and the design, justification, and implementation of the technologies reformatting this encounter from key locations within state agencies. Emerging technological infrastructures for social welfare do not simply reconfigure how existing services are offered and accessed. They facilitate the identification of new target populations for intervention, at the same time that they introduce additional burdens, hurdles and forms of intervention and surveillance for these populations. As such, it is evident in the design and application of these technologies that they accord with and expedite punitive logics in welfare provision, providing new opportunities for the application of dominant neoliberal governance strategies. In both arenas, one can conceptualize ‘pipelines’ for the implementation of these developments. These pipelines are interstitial and heterogeneous, and combine different timelines, technologies and actors. They are often technically or administratively opaque or otherwise obscured from view. This gives rise to a methodological and intellectual problem, around the extent to which researchers can say they know enough to point to determining instances, political agendas, commercial agreements, incidental alignments and so on in such a way as to advocate effectively for democratic input and oversight. In this sense the papers assembled highlight how these developments call for new politics of method, new modalities of analysis and critique, and more effective activist and academic engagements with the question of how ideals of justice and equity can best be instantiated in these contexts.